Determinantes da adoção da tecnologia de controle biológico da mosca-branca com o fungo Cordyceps javanica - Borges, Mariely Moreira (2023)
The excessive application of pesticides has had negative effects, not only on nature, water quality and food security, but also on human health. In addition, the growing resistance of insects to chemical insecticides has made it difficult to control pests such as the whitefly. Among the 17 Sustainable Development Goals (SDGs) chosen by the UN, the second aims to eliminate hunger, ensure food security, increase nutrition and promote sustainable agriculture. The goal is to double agricultural productivity and the income of small food producers by 2030, in addition to securing food production systems and implementing resilient agricultural practices. In view of this, it is essential to expand integrated pest management strategies, including biological control. Lallemand and EMBRAPA, together, formulated a biological product based on the fungus Cordyceps javanica, known as Lalguard Java. The objective of this work is to evaluate which factors are involved in the adoption of this biological product. Through a qualitative and quantitative research that used groups. Most seniors have low education, in addition to this there is a clear difficulty in accessing quality information, which can negatively influence the adoption of new technologies. Products that know the effectiveness of biological control are 81.81% more likely to adopt biological control with the fungus LALGUARD JAVA if it is efficient in controlling the whitefly and if it does not cause harm to humans and the environment. Producers who know the effectiveness of biological control have a 135.57% greater chance of adopting biological control with the fungus LALGUARD JAVA if it presents a cost and mortality level similar to those of chemical control.